Alcohol-induced gut permeability defect through dysbiosis and enterocytic mitochondrial interference causing pro-inflammatory macrophages in a dose dependent manner - Wiwat Chancharoenthana; Supitcha Kamolratanakul; Kanyarat Udompornpitak; Dhammika Leshan Wannigama; Marcus J. Schultz; Asada Leelahavanichkul (Scientific Reports)
Abstract Although toxicity of alcohol toward the intestines and immunity is mentioned, there might be different effect of alcohol in a low and a high dose and the rodent model development using a simple SHIRPA binary score night be useful. Hence, a low and high dose of alcohol (6.30 and 1.26 g/kg/day) were administered in might for 16 weeks before determination of several parameters. As such, the peak blood alcohol concentration (BAC) of low and high dose of alcohol were approximately at 0.05 and 0.15%, respectively, at 1 h post-administration, which correlated with SHIRPA score at 1.8 ± 0.8 and 7.2 ± 0.6, respectively. After 16 wk of administration, a significant liver injury in high-dose alcohol was indicated by liver enzymes, liver weight, histology score, apoptosis, and hepatic accumulation of triglyceride (TG) and oxidative stress (malondialdehyde; MDA) with reduced anti-oxidant (glutathione). Meanwhile, low-dose alcohol demonstrated only elevated apoptosis with increased TG and MDA in liver tissue. Leaky gut from both dose of alcohol was also demonstrated by FITC-dextran, endotoxemia, serum beta glucan, and reduced occludin. However, bacterial abundance (microbiome analysis) of the feces from small bowel of high-dose alcohol, but not the low dose, was different from the control (increased Alitipes spp. with reduced Lachnospiraceae). In conclusion, both low- and high-dose alcohol induced leaky gut, while only the high-dose caused gut dysbiosis and alcohol damaged mitochondria but enhanced glycolysis in enterocytes and macrophages. Leaky gut might be more sensitive than dysbiosis to determine alcohol-induced intestinal injury.